PENERAPAN PROBIOTIK PADA KELOMPOK PEMBUDIDAYA IKAN LELE DI SMP TARUNA JAYA 1 SURABAYA - Syifania Hanifah Samara; Yudi Cahyoko; Muhamad Amin (Universitas Mataram, 2026)
Catfish (Clarias sp.) is an important fishery commodity in Indonesia. Seeing the potential of catfish, a group of teachers and students at Taruna Jaya 1 Middle School Surabaya attempted to utilize the school grounds for catfish cultivation activities as a learning tool for students. However, the implementation of catfish cultivation itself still faces many obstacles, the most important of which is the high cost of feed. Therefore, the community service team of the Department of Aquaculture, Faculty of Fisheries and Marine Sciences, Airlangga University took the initiative to introduce the use of probiotics in catfish cultivation to a group of teachers at Taruna Jaya 1 Middle School Surabaya, through mentoring. This mentoring was carried out in four activities: surveys, socialization of probiotic use in catfish, demonstrations of their use, and evaluations. The mentoring activity of optimizing freshwater fish cultivation by providing probiotics in feed at Taruna Jaya 1 Middle School Surabaya was carried out well. Through this activity, the school community there also gained knowledge and skills related to the application of probiotics in catfish cultivation. This is shown in the results of the pretest, which was previously 20%, and increased to 90%. This activity is expected to increase the productivity of catfish farming there and provide teachers and students with the necessary skills to effectively conduct cultivation activities. The school is expected to continue implementing probiotics in catfish farming activities at Taruna Jaya 1 Middle School Surabaya.